ERN1 dependent impact of glucose and glutamine deprivations on PBX3, PBXIP1, PAX6, MEIS1, and MEIS2 genes expression in U87 glioma cells - Krasnytska Dariia O.; Viletska Yuliia M.; Minchenko Dmytro O.; Khita Olena O.; Tsymbal Dariia O.; Cherednychenko Anastasiia A.; Kozynkevych Halyna E.; Oksiom Nataliia S.; Minchenko Oleksandr H. (Endocrine Regulations, 2023)
Objective. Homeobox genes play a fundamental role in the embryogenesis, but some of them have been linked to oncogenesis. The present study is aimed to investigate the impact of glucose and glutamine deprivations on the expression of homeobox genes such as PAX6 (paired box 6), PBX3 (PBX homeobox 3), PBXIP1 (PBX homeobox interacting protein 1), MEIS1 (MEIS homeobox 1), and MEIS2 in ERN1 knockdown U87 glioma cells with the intent to reveal the role of ERN1 (endoplasmic reticulum to nucleus signaling 1) signaling pathway on the endoplasmic reticulum stress dependent regulation of homeobox genes.